2019
DOI: 10.1016/j.ebiom.2019.04.044
|View full text |Cite
|
Sign up to set email alerts
|

DsbA-L ameliorates high glucose induced tubular damage through maintaining MAM integrity

Abstract: Background The mitochondrial associated endoplasmic reticulum (ER) membrane (MAM) provides a platform for communication between the mitochondria and ER, and it plays a vital role in many biological functions. Disulphide-bond A oxidoreductase-like protein (DsbA-L), expressed in the MAM, serves as an antioxidant and reduces ER stress. However, the role of DsbA-L and MAM in kidney pathobiology remains unclear. Methods Molecular biology techniques, transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 50 publications
4
62
0
Order By: Relevance
“…To our knowledge, we are the first to have found that tubular DsbA-L mediated UUO-induced TIF, renal cell apoptosis, and inflammation in mice. It is completely opposite to the role of DsbA-L in DN 17,18 ; the possible reason is that the difference between the role of system and tubular KO DsbA-L in DN and UUO model. In addition, we also found that DsbA-L mediated I/R, low-dose cisplatin, and aristolochic acid-induced TIF.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, we are the first to have found that tubular DsbA-L mediated UUO-induced TIF, renal cell apoptosis, and inflammation in mice. It is completely opposite to the role of DsbA-L in DN 17,18 ; the possible reason is that the difference between the role of system and tubular KO DsbA-L in DN and UUO model. In addition, we also found that DsbA-L mediated I/R, low-dose cisplatin, and aristolochic acid-induced TIF.…”
Section: Discussionmentioning
confidence: 85%
“…Ziviani (2018) demonstrated that Parkin alters MAMs integrity by affecting the ubiquitination of MFN2 ( Basso et al, 2018 ). Recently, our group also verified that disulfide-bond A oxidoreductase-like protein (DsbA-L), which is a 25-kDa antioxidant enzyme that is also located in MAMs, inhibits the apoptosis of tubular cells in diabetic nephropathy by maintaining MAMs integrity ( Yang et al, 2019 ; Figure 1 ). Under pathological conditions, the increase or decrease in ER-mitochondria connections caused by various factors leads to dysregulated intracellular communication signaling.…”
Section: Mams Tethers In Mammalian Cellsmentioning
confidence: 76%
“…In fact, the IP3R-VDAC1 complex is the core structure for calcium ion transport in MAMs, and this protein complex is also a marker of MAMs. We can use an in situ proximity ligation assay (PLA) to detect the integrity of the IP3R-VDAC1 complex to quantify MAMs ( Tubbs and Rieusset, 2016 ; Zhu et al, 2017 ; Yang et al, 2019 ). In addition, the split-GFP-based contact site sensor (SPLICS) probe from the Cali laboratory can be used to measure the coupling between the ER and mitochondria ( Cieri et al, 2018 ).…”
Section: Mams Tethers In Mammalian Cellsmentioning
confidence: 99%
“…Additionally, despite the high energy demand and abundant mitochondria content that make proximal tubular epithelial cells (PTECs) very vulnerable to mitochondrial dysfunction in DKD, no study has yet verified this scenario in tubular cells, especially in the PTECs. However, our recent study reached an opposing conclusion regarding MAMs formation, in which we found that MAMs formation was decreased in the tubules of patients and mice with DKD, and maintaining MAMs integrity via the DsbA-L/Mfn2 axis reduced tubular apoptosis, which also supported a protethering role of Mfn2 [ 74 ]. One plausible interpretation for this conflicting finding is that reduced MAMs at the latter stage of DKD would be detrimental to tubular survival, considering initially appropriated MAMs increase boosts in mitochondrial respiration and bioenergetics.…”
Section: Modulation Of Mitochondrial Quality Controlmentioning
confidence: 86%
“…Regarding strategies used to disrupt MAMs, manipulation of FATE1 expression might be the preferred alternative, because FATE1 expression is mainly restricted to the testis, adrenal gland, and in a variety of cancers [ 46 ]. FATE1 overexpression has also been successfully performed to reduce MAMs in human myotubes [ 58 ] and in human proximal tubular cells (HK-2) [ 74 ].…”
Section: Mams: Assessment and Manipulationmentioning
confidence: 99%